A CMOS Quadrature Signal Generator for Impedance Spectroscopy Measurement Systems - Márquez Marzal, Alejandro; Medrano Marqués, Nicolás; Calvo López, Belén; Martínez Martínez, Pedro A. (Jornada de Jóvenes Investigadores del I3A, 2018)
A CMOS fully integrated quadrature signal generator for on-chip impedance spectroscopy (IS) applications is presented. Frequency can be digitally tuned from 5 to 350 kHz with 12-bit resolution. Power consumption is 0.77 mW and active area is 0.129 mm2. Its suitability for the target application is validated with a Randles test impedance cell modelling a protein.